Efficient Removal of Phosphate from Aqueous Solutions Using Kaolin-Supported Nanoscale Zero-Valent Iron Particles - Timurtas, Merve; Tunc, Muslun Sara (Springer Int Publ Ag, 2024)
In this study, kaolin-supported nanoscale zero-valent iron (K-nZVI) was tested as an adsorbent for the removal of phosphate from aqueous solutions. The influences of various parameters, including the kaolin to nZVI mass ratio, the solution's initial pH, the amount of K-nZVI, the initial phosphate concentration and various anions on the phosphate removal by K-nZVI were investigated. The optimum K-nZVI amount and initial pH at the initial phosphate concentration of 16 mg P/L were 0.5 g/L and pH 3, respectively, corresponding to a phosphate removal of 98.75%. The highest phosphate adsorption capacity was determined to be 82.19 mg P/g for an initial phosphate concentration of 62 mg P/L at pH 3 and 45 degrees C. The adsorption isotherm and kinetic followed the Freundlich and pseudo-second-order (PSO) models, respectively. A thermodynamic study demonstrated that the phosphate adsorption onto K-nZVI is spontaneous as well as endothermic. In the presence of sulfate, nitrate, and chloride anions, no phosphate removal was blocked. Instead, the removal was negatively impacted by the presence of the bicarbonate anion. The maximum phosphate desorption of 65.5% was achieved at pH 13. The results indicated that K-nZVI can be used as an efficient material for treating phosphate-rich waters.
Keywords: Adsorption; Eutrophication; Kaolin; Isotherm and kinetics; Nanoscale zero-valent iron (nZVI); Phosphate removal